(untitled) (Journal of Philosophy Culture and Political Science, 2021)
Communications mediated by digital devices acquire moral, ethical and axiological significance. It is necessary to find out how live human communication is being transformed into the digital age. What communication model is typical for our time? Is culture being deconstructed or does it still retain the honorable right to generate meanings? Postmodern philosophy as a methodological principle can be applied to study the processes of transformation of the communication and technological landscape of our time. Modern culture can be described as mosaic. Like hypertext systems, it does not have a center-forming principle. In conditions of information redundancy, we are doomed to a constant search for values. Maybe in order to comprehend the meaning, we need to bring the process of disintegration of the text to its logical end, disassemble and reassemble it. Having designated the "absence" of strict meanings, come to a unified view of the world. Key words: text, hypertext, culture, postmodernism, communication